Prolactin as an inhibitor of granulosa cell luteinization: implications for hyperprolactinemia-associated luteal phase dysfunction - Adashi, Eli Y.; Resnick, Carol E. (Fertility and sterility, 1987)
Chronic and transient hyperprolactinemia have been associated with luteal phase dysfunction in both spontaneously cycling women and those subjected to ovarian hyperstimulation by exogenous gonadotropins. It is the objective of the in vitro and in vivo studies reported herein to examine the possibility that prolactin (PRL), a known constituent of ovarian follicular fluid, may account, at least in part, for the luteinization inhibitory (LI) activity exerted by follicular fluid (FF) under both physiologic and pathophysiologic circumstances. In vitro treatment with human PRL (100ng/ml) reduced by 57% the specific binding of luteinizing hormone (LH) to follicle-stimulating hormone(FSH)-primed cultured rat granulosa cells, an effect associated with a 2.6-fold diminution of human chorionic gonadotropin (hCG; 10ng/ml)-stimulated progesterone biosynthesis. Importantly, the ability of PRL to exert a direct inhibitory effect on FSH-supported LH binding was fully reproduced under in vivo conditions. Inasmuch as the acquisition of LH receptors and progesterone (P) biosynthetic capacity are acceptable as criteria of granulosa cell luteinization, the authors’ findings indicate that PRL, acting at concentrations achievable in vivo within the ovarian FF, may account, if only in part, for physiologically encountered LI-like activity. Moreover, subject to limitations imposed by the rat model employed, consideration also must be given to the possibility that hyperprolactinemia-associated luteal phase dysfunction may not only reflect the suppressive effect(s) of PRL at the central level of the reproductive axis, but may also be due, at least in part, to the consequences of inappropriately elevated PRL at the level of the follicular microenvironment.